Clinical Aspects of Primary Hyperparathyroidism - Jan, Mian Asadullah; Falah, Sheikh Qais (Journal of Postgraduate Medical Institute, 2011)
We present 4 cases of primary hyperparathyroidism presenting with patholgoical fracture. All of them were females with age range of 26 - 37 years. The average time for which they remained symptomatic before diagnosis was made in 2 years. Ultrasound abdomen showed renal claculi in all. Serum calcium was in the normal range in 2 of the cases. Serum PTH assay was elevated and para-thyroid Scinti-scan was positive in all cases. Bilateral neck exploration was the procedure carried out on all of them. Parathyroid adenoma was the underlying cause in all the cases as confirmed on histopathology.